Energy Saving Innovation, Vintage Capital, and the Green Transition - Christian Keuschnigg; Giedrius Kazimieras Stalenis (CESifo GmbH, 2025)
We study a small open economy that must implement an emissions reduction plan and eventually phase out fossil fuel. R&D leads to the design of energy saving new machines. Endogenous scrapping eliminates old inefficient machines. We identify two distortions that delay the adoption and diffusion of energy saving technology: scrapping of old equipment and investment in new machines are both too low. The optimal policy to manage the energy transition thus combines a carbon tax with a profit tax to speed up exit, and an investment subsidy to speed up investment in new equipment. The optimal policy increases capital turnover, the diffusion of energy saving technology, and thereby mitigates the costs of the energy transition. Compared to a policy that exclusively relies on carbon taxes, the optimal policy could reduce the GDP loss of moving to net zero from 7.8 to 6.1% of GDP.
Keywords: D21; D62; H23; O33; Q41; Q43; 330; energy saving innovation; vintage capital; emissions reduction